An Assessment of The Effect of Processing on The Proximate Constituents of Blood Meal Sourced From Cattle And Goat in Zaria, Nigeria - Omoniyi, K. I.; Ekwumemgbo, P. A.; Orunmuyi, M.; Yerima, E. A. (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
The work reports the proximate and mineral composition of non-steam processed and processed samples of blood meal sourced from cattle and goat (n = 5) in Zaria, Nigeria using standard analytical techniques. The blood samples were processed by steam coagulation at a temperature of 100oC for 45 mins, and the solid obtained sun-dried. The ranges of the percentage moisture of the non-steam processed blood meal from cattle and goat were 12.02 13.59 % and11.01 11.09 %; ash 2.21-2.91 % and 2.00-2.22 %; crude lipid 1.05-1.79 % and 0.72-1.70 %; crude fibre 0.49-0.56 % and 0.51-1.15 % and crude protein 80.75-83.57 % and 83.57 - 85.09% respectively. After processing, the ranges of the moisture content of the blood meals from cattle and goat were 8.99-10.08 % and 8.51-9.99 %; ash 7.15-9.99 % and 7.33-9.91 %; crude lipid 2.24-2.97 % and 2.69 -2.90 %; crude fibre 0.05-0.07 % and 0.01-0.04 %; and crude protein 75.98-80.01% and 74.94-80.20% respectively. The calcium and phosphorus content of the un-processed meal were in the range 344.9-550.5 mg/kg and 430-559 mg/kg for cattle and 293-728 mg/kg and 688-818 mg/kg for goat. Ca and P levels after processing were 6482-8835 mg/kg and 918-1234 mg/kg for cattle, 7536-11090 mg/kg and 1306-1837 mg/kg for goat. The Ca/P ratio, density, acidity, ash content and crude lipid were elevated in the blood meals sourced from cattle and goat as a result of steam processing. Processing of blood meal had no significant difference in pH value of the meal sourced from cattle, but had for goat. Blood meal from cattle and goat are equally enriched with the determined nutritional and mineral contents.